The Effect of Education on Poverty: A European Perspective - Thomas Hofmarcher (Lund University, School of Economics and Management, Department of Economics, 2019)
This paper provides evidence on the causal relationship between education and poverty. I construct a novel database comprising compulsory schooling reforms in 32 European countries and use them as instruments for education. I find economically large poverty-reducing effects of education among people aged 30 to 80. This holds true for both objective measures of poverty (relative income poverty, lack of basic necessities, weak labor market attachment) and a subjective measure of poverty (self-assessed difficulties in making ends meet). An additional year of education thus reduces not only the likelihood of being classified as living in poverty but also the likelihood of considering oneself to live in poverty. Increases in labor force participation and full-time employment as well as better health are potential mechanisms behind these results.
Keywords: I24; I26; I32; 330; poverty; education; compulsory schooling; social exclusion